2007
DOI: 10.1002/ptr.1962
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral triterpenoids from the medicinal plant Schefflera heptaphylla

Abstract: Schefflera heptaphylla (L.) Frodin is a principal ingredient of an herbal tea formulation widely used for the treatment of common cold in southern China. An extract of the long leafstalk of the compound leaf of S. heptaphylla exhibited the most potent antiviral activity against respiratory syncytial virus (RSV). Further antiviral-guided fractionation and isolation of the leafstalk extract of S. heptaphylla led to obtain two highly active pure triterpenoids, namely 3alpha-hydroxylup-20(29)-ene-23,28-dioic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 21 publications
(24 reference statements)
1
41
0
2
Order By: Relevance
“…Oleanolic acid (13) was identified as an anti-HIV principle from several plants, including Rosa woodsii (leaves), Prosopis glandulosa (leaves and twigs), Phoradendron juniperinum (whole plant), Syzygium claviflorum (leaves), Hyptis capitata (whole plant) and Ternstromia gymnanthera (aerial part). It inhibited HIV-1 replication in acutely infected H9 cells with an EC 50 value of 1.7 μg/mL and inhibited H9 cell growth with an IC 50 value of 21.8 g/mL (TI 12.8) [15].…”
Section: Triterpenes and Sterolsmentioning
confidence: 99%
See 2 more Smart Citations
“…Oleanolic acid (13) was identified as an anti-HIV principle from several plants, including Rosa woodsii (leaves), Prosopis glandulosa (leaves and twigs), Phoradendron juniperinum (whole plant), Syzygium claviflorum (leaves), Hyptis capitata (whole plant) and Ternstromia gymnanthera (aerial part). It inhibited HIV-1 replication in acutely infected H9 cells with an EC 50 value of 1.7 μg/mL and inhibited H9 cell growth with an IC 50 value of 21.8 g/mL (TI 12.8) [15].…”
Section: Triterpenes and Sterolsmentioning
confidence: 99%
“…Frodin is a principal ingredient of an herbal tea (Schefflera heptaphylla) formulation widely used for the treatment of common cold in southern China [13]. An extract of the long leafstalk of the compound leaf of S. heptaphylla exhibited the most potent antiviral activity against respiratory syncytial virus.…”
Section: Triterpenes and Sterolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another equally interesting group of chemical compounds that suppress the adsorption of viruses can be called triterpene saponins and steroids. These compounds are capable of changing the spatial structure of the cell membrane because of its structural features by binding with membrane cholesterol [15,16].…”
Section: Viral Adsorption and Penetrationmentioning
confidence: 99%
“…Thus, there is an urgent need for the development of effective and safe vaccines and therapeutics. Previous studies showed inhibition of hRSV by several natural compounds, including amentoflavone [9]; anagyrine, oxymatrine, sophoranol, wogonin, and oroxylin A [10]; 3-alpha-hydroxy-lup-20(2 9)-ene-23,28-dioic acid and 3-epi-betulinic acid 3-O-sulfate [11]; and cimicifugin [12]. …”
Section: Introductionmentioning
confidence: 99%